Evaluation of aerobic capacity in soccer players: comparison of field and laboratory tests - Alemdaroglu, U. B.; Dündar, U.; Köklü, Y.; Asci, A. (Biology of Sport, 2012)
The purpose of this study was to evaluate the maximal oxygen uptake ( ·VO2max) values in soccer players as assessed by field and laboratory tests. Fourteen amateur soccer players (mean age: 21.9 ± 2.5) performed 2 maximal field tests: the Yo-Yo intermittent recovery test level 1 (YIRT), and the 20-m multi-stage shuttle run test (MST), as well as 1 maximal test on the treadmill with the Bruce treadmill test (BTRT) protocol. A portable telemetric ergospirometry device was used during all the tests to determine ·VO2max. In addition, an estimated ·VO2max value was calculated for players after all the tests. At the end of the study, no significant differences were found between field and laboratory tests in terms of measured ·VO2max, HRmax and respiratory exchange ratio (RER) (p>0.05), whereas significant differences were found between field and laboratory tests in terms of estimated ·VO2max (p<0.05). In addition, there were no significant differences between measured ·VO2 and estimated ·VO2max in BTRT, whereas significant differences were found between measured ·VO2max and estimated ·VO2max in both YIRT and MST. Finally, while there was a strong relationship between ·VO2max and both MST and BTRT performance (distance covered), there was a moderate correlation between ·VO2max and YIRT performance. This study results suggest that it is necessary to use ergospirometry to accurately estimate aerobic capacity in soccer players. In addition, both MST and YIRT could be used to determine HRmax of players, and MST has a strong relationship with ·VO2max. Thus MST may also be a more favourable field-based assessment of soccer players` endurance performance.